GIS TOOLS IN THE WORK OF EPIDEMIOLOGICAL DIVISION OF SPECIALIZED ANTI-EPIDEMIC FORMATION DURING OBJECT EXERCISE OF LOCALIZATION A CHOLERA IMPORTED FOCUS - E. S. Kulikalova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The results of the object exercise of the Specialized Anti-Epidemic Formation (SAEF) of Irkutsk Antiplague Research Institute performed in July 2011 are summarized. According to the exercise plan, SAEF subdivisions carried out tasks on monitoring of surface waters in conditions of an imported, cholera focus. GIS (Geo-Informational Systems)-technologies and. GPS-navigation were used, for optimization, the SAEF actions. Algorithm of measures on the basis of the epidemic significance of vibrios isolated, from surface waters was developed.